2018
DOI: 10.1093/pubmed/fdy126
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive decline and alcohol consumption adjusting for functional status over a 3-year period in French speaking community living older adults

Abstract: Alcohol consumption did not contribute to cognitive decline. Cognitive decline was greater in individuals reporting low functional status. Research should focus on the interaction between changing patterns of alcohol consumption and social participation in individuals with low and high functioning status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The social support of the participants was assessed with three questions previously used as covariables to measure the impact of alcohol consumption on the mental state in a study conducted in Canada [ 27 ]. Participants were considered to have social support if they answered yes to the three questions or no social support if they answered yes to 0 to 2 questions.…”
Section: Methodsmentioning
confidence: 99%
“…The social support of the participants was assessed with three questions previously used as covariables to measure the impact of alcohol consumption on the mental state in a study conducted in Canada [ 27 ]. Participants were considered to have social support if they answered yes to the three questions or no social support if they answered yes to 0 to 2 questions.…”
Section: Methodsmentioning
confidence: 99%
“…One cohort study found a dose-depended positive association for alcohol use and cognition compared to abstainers and former drinkers [ 74 ]. Another cohort study revealed significant cognitive impairment in low-functioning non-drinkers and light-to-moderate drinkers and high-functioning non-drinkers [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…One cohort study found doseresponse positive association of alcohol use and cognitive function compared to abstainers and former drinkers [80]. Another cohort study revealed significant cognitive impairment in low functioning non-drinkers and light to moderate drinkers and high functioning nondrinkers [81].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%